Wpływ informacyjny telewizyjnych reklam wyborczych w świetle deklaracji polskiego elektoratu – studium kampanii wyborczych 2015 - Olszanecka-Marmola, Agata (Political Preferences, 2016)
The cognitive effect of TV political advertising in view of Polish electorate – case of 2015 presidential and parliamentary campaigns Apart from persuasive function, TV political ads play also important role in obtaining information about candidates and political parties. The cognitive effect of TV political advertising is proved in American and West-European conditions. Presented article is aimed at examining whether TV political spots influenced on voters’ knowledge of candidates and parties contesting in 2015 elections in Poland. The results of research will be presented with reference to sociodemographic characteristics of electorate, political preferences and auto-identifications on left-right scale. Key words: political advertising, TV political ads, cognitive effect of TV political ads, 2015 presidential election in Poland, 2015 parliamentary election in Poland